In Vitro Comparison of the Antimicrobial Effect of Turmeric and Cinnamon Water and Ether Extracts on the Growth Rate of Helicobacter Pylori - E Norizadeh; B Shokoohi; S Latifi Navid (Tehran University of Medical Sciences, 2007)
Background: Nowadays, it has been known that Helicobacter pylori (H. pylori) is causative agent of the most common GI infection in world; at least half of the populations of many communities are affected by this bacterium. H. pylori infection plays an important role in progression of gastritis and especially in the peptic ulcers of duodenum. Eradication of H. pylori has lead to a significant decrease in the prevalence of PUD world-wide. At present, due to various reasons, such as to overcome bacterial resistances, it seems that the investigation for production of new antibacterial products is a necessity. So, this study was designed to evaluate the "in vitro" inhibitory effects of ether and water extracts of turmeric and cinnamon on the growth of H. pylori. Methods: Ether and water extracts of Turmeric and cinnamon was investigated by agar dilution and disc diffusion methods on five strains of H. pylori. Results: Ether and water extracts obtained from the studied plants have antibacterial effects and water extract of turmeric represented the most potent antibacterial effect. Conclusion: The results showed that the investigated plants have antibacterial capacity; in this case, cinnamon water extracts have a considerable antibacterial effect on H. pylori. Therefore, more investigation on this plant is recommended, by extraction of its effective materials. Abbreviations: H. pylori, Helicobacter pylori; ASR, age standardized rate; MIC, minimum inhibitory concentration; GI, gastrointestinal; PUD, peptic ulcer disease; DNA, deoxyribonucleic acid